A systematic review of Clostridium difficile infection following reversal of ileostomy. (3rd October 2017) - Harries, R. L.; Ansell, J.; Codd, R. J.; Williams, G. L.
Abstract: Aim: The incidence of Clostridium difficile infection (CDI) has been reported to be as high as 4% following ileostomy reversal. CDI can be associated with significant morbidity. A systematic review on this subject has not been previously reported; our aim was to review the literature to establish incidence and to evaluate the factors that may contribute to an increased risk of CDI following ileostomy reversal. Method: A systematic review of Ovid, Embase and Medline was undertaken. Search terms included C. difficile, reversal of ileostomy and ileostomy closure. Articles were included where at least one case of C. difficile ‐associated diarrhoea following reversal of defunctioning ileostomy was reported. Data extraction for articles was performed by two authors, using predefined data fields. The primary outcome measure was incidence of CDI amongst patients undergoing ileostomy reversal. Secondary outcomes were defunctioning time, antibiotic regime, acid suppression, time to onset of symptoms and study conclusions including colectomy and mortality rate. Results: Eleven articles were included (five case reports and six cohort studies). The overall incidence of CDI was 1.8% (242/13 728). The mean defunctioning time was 8.7 months (range 6–12). A variety of antibiotic regimes were described. Mean time to onset of symptoms was 6 days (range 3–14). Use of acid suppression, colectomy or mortality rate were frequently not reported. Conclusion: CDI should be recognized as a potentially life‐threatening complication of ileostomy closure. Careful consideration should be given to peri‐operative antibiotic regime, acid suppression, timing of reversal and appropriate preoperative counselling of patients.